2022
DOI: 10.1039/d1qi01442k
|View full text |Cite
|
Sign up to set email alerts
|

Computational predictions of adaptive aromaticity for the design of singlet fission materials

Abstract: Singlet fission has attracted extensive attention from experimentalists and theoreticians due to its ability to improve photovoltaic conversion efficiency. Still, designing singlet fission materials remains challenging. In this work, we...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 114 publications
0
20
0
Order By: Relevance
“…21,22 The presence of adaptive aromaticity is very useful and, for example, could help design the singlet fission materials. 20,23,24 It is worth noting that the origin of aromaticity should not be limited to the p-electron delocalization. In 1970s, Dewar first proposed the concept of s-aromaticity to rationalize the unusual magnetic behavior of cyclopropane based on the skeletal s-electrons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,22 The presence of adaptive aromaticity is very useful and, for example, could help design the singlet fission materials. 20,23,24 It is worth noting that the origin of aromaticity should not be limited to the p-electron delocalization. In 1970s, Dewar first proposed the concept of s-aromaticity to rationalize the unusual magnetic behavior of cyclopropane based on the skeletal s-electrons.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 The presence of adaptive aromaticity is very useful and, for example, could help design the singlet fission materials. 20,23,24…”
Section: Introductionmentioning
confidence: 99%
“…15 In 2020, the concept of adaptive aromaticity was applied to the singlet fission in a pyrrole-fused skeleton, which highlights the application of adaptive aromaticity to material science. 16 Very recently, DFT calculations revealed that species with adaptive aromaticity in most cases satisfy the thermodynamic requirements of the singlet fission process, 17 suggesting great potential of this concept in designing singlet fission materials.…”
Section: Introductionmentioning
confidence: 99%
“…In recent academic studies, Huan et al explored the lithiation process of the P5Q cathode based on density functional theory (DFT) for the first time. [25][26][27][28][29] All lithiated structures of P5Q were compared, and the lowest energy one was selected to predict the possible Li-binding site. However, it is time-consuming and some possible product structures could be neglected easily.…”
Section: Introductionmentioning
confidence: 99%